Effect of C:N Ratio Levels on Water Quality and Shrimp Production Parameters in Penaeus monodon Shrimp Culture with Limited Water Exchange Using Molasses as a Carbon Source - Pohan Panjaitan (Marine Science Department Diponegoro University, 2011)
The main obstacles in developing intensive shrimp culture is waste of shrimp farms which is detrimental to environment. Mitigating the environmental impacts of effluent discharge, shrimp culture should be implemented in closed system with limited water exchange. However, the major problem associated with limited water exchange system is the rapid deterioration in pond, resulting from increasing concentration ammonia and nitrite. The addition of carbon materials such as molasses into shrimp culture with manipulating the carbon : nitrogen ratio level is one of the best strategies of controlling ammonia and nitrite in shrimp culture with Limited Water Exchange Model (LWEM). Therefore, the principal aim of this study was to evaluate the effects of C:N ratio levels on water quality and shrimp production in Penaeus monodon shrimp culture with Limited Water Exchange Model (LWEM) using molasses as a carbon source. Study reveals that C:N ratio levels significantly effected on water quality and shrimp production parameters of shrimp culture with LWEM using molasses as carbon resource using molasses. Key words: C: N ratio level, water quality, limited water exchange model, molasses Hambatan utama di dalam pengembangan budidaya udang intensif adalah limbah tambak udang yang merusak lingkungan. Mengurangi dampak lingkungan buangan limbah, budidaya udang seharusnya dilakukan di sistem terbuka dengan pergantian air terbatas.Namun, masalah utama yang terakit dengan system pergantian air terbatas adalah penurunan kolam cepat akibat meningkatnya konsentrasi ammonia dan nitrit. Penambahan bahan karbon contohnya molasses ke tambak dengan mengatur level rasio karbon : nitrogen merupakan suatu stategi terbaik untuk mengontrol ammonia dan nitrite di budidaya udang dengan model pergantian air terbatas. Dengan demikian, tujuan utama studi ini adalah untuk mengevaluasi pengaruh level C:N ratio terhadap parameter kualitas air dan produksi udang di budidaya udang Penaeus monodon dengan menggunakan model pergantian air terbatas. Studi menunjukkan bahwa level C:N ratio berpengaruh nyata terhadap parameter kualitas air dan produksi udang di budidaya udang dengan model pergantian air terbatas. Kata kunci: Level rasio C:N, kualitas air, model pergantian air terbatas, molasses